Consumers’ attitude towards “mamak” food in Malaysia - Abu Bakar, K.; Farinda, A.G. (2012)
Malaysia is a unique country. There are various races and ethnics of people living together in harmony and as such there are many ethnic foods for example “Mamak” food. “Mamak” food is popular among Malaysian and can be found from roadside stalls to café or bistro concept restaurants. The objective of this study is to provide an insight into customers dining intention to “Mamak” restaurants measuring the service quality and food attributes. A questionnaire survey was administered in this study and result showed that only one of the factor of service quality that is assurance and one variable of food attributes that is aroma, have greater influence on customers dining intention. The findings in this study can be used by other concepts restaurants to develop a competitive advantage that will further promote Malaysia as an interesting and colorful gastronomic tourism destination in the world.